A study on assessment and analysis of new born hearing screening by otoacoustic emission - Sureshrajkumar, S.; Ravisankar, V. (International Journal of Contemporary Pediatrics, 2022)
Background: Hearing impairment can occur at any age, but the most severe one appears before or immediately after birth. The consequences of these damages can cause speech and intellectual development function disorders. Test like otoacoustic emission (OAE) is required for newborn for early neonatal screening, hence aim of our study is to evaluate the incidence of early hearing loss using OAE in new born. Methods: This is a prospective study done in new born delivered in PSG medical college and hospital during the study period of one year in 2018. Our sample size was 1040. All new born between 36 hours and 28 days born in this hospital were included. A pre-designed, pre-tested validated semi-structured proforma was used to record the findings. Results: In our study prevalence of deafness was found to be 0.19%. Out of 48 high risk babies, one baby (2.1%) had hearing impairment (profound hearing loss), similarly out of 992 non-high-risk babies, there was one baby with hearing impairment. Out of 1040 babies, 186 babies have failed OAE test at 36 hours of birth. Out of those 186 babies, test at two weeks of birth 84 failed and 102 passed and at 28 days- 72 babies passing and 12 babies were failing the test. Twelve babies were subjected to brainstem evoked response audiometry (BERA) test where only two babies out of 12 babies turned out to be BERA positive. Conclusions: Hence, early identification and intervention will allow deaf and hard of hearing children to develop language skills during a period of neural plasticity.